Analisis Volume Modal Kerja dan Fluktuasi Laba pada Usaha Dagang Pisang Agung Lumajang - Istichomah, Istichomah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
This research is used, so that business owners can find out the development of the volume of working capital and fluctuations in the level of profits in the company. Case studies carried out in wood management at UD. Agung Lumajang Banana. This test is carried out on the financial situation that lasted for three years from 2015 to 2017 and this study no other wants to know the volume of working capital and fluctuations in the level of profit using existing formulas to analyze it. The results showed that in 2015 it began with a capital of IDR 525,000,000.00 which then decreased in the following year namely 2016 to IDR 482,000,000.00 and experienced a significant increase in the following year 2017 to IDR 630,000,000, 00. For the development of profit levels in 2015, gross profit of IDR 210,000,000.00 with sales of IDR 1,152,0145,000.00 with a percentage rate of 18.21% in the following year 2016 gross profit of IDR 225,000,000.00 with sales of IDR 1,254,260,000 , 00 with a percentage level of 17.93%, the results indicate a decrease in that period, in the following year 2017 gross profit of IDR 235,000,000.00 means experiencing an increase in sales of IDR 1,275,358,000.00 with a percentage of 18.42%. Based on the results of the analysis that, working capital is an element that plays a role in generating income, while profit can determine the level of achievement of the company. The increase in sales figures does not always increase the level of profits received by the company. For this reason, the management must ensure that the level of effectiveness and efficiency of the company is directly proportional to the company's sales because the sales of the company do not always increase the level of corporate profits in the same year. Researchers hope for further research to expand or describe the research by adding other factors that affect the volume of working capital and fluctuations in the level of profits.